A Survey of Copy Number Variation in the Porcine Genome Detected From Whole-Genome Sequence - Keel, Brittney N.; Nonneman, Dan J.; Lindholm-Perry, Amanda K.; Oliver, William T.; Rohrer, Gary A. (Frontiers in Genetics, 2019)
Copy number variations (CNV) are gains and losses of large regions of genomic sequence between individuals of a species. Although CNV have been associated with various phenotypic traits in humans and other species, the extent to which CNV impact phenotypic variation remains unclear. In swine, as well as many other species, relatively little is understood about the frequency of CNV in the genome, sizes, locations, and other chromosomal properties. In this work, we identified and characterized CNV by utilizing whole genome sequence from 240 members of an intensely phenotyped experimental swine herd at the U.S. Meat Animal Research Center (USMARC). These animals included all 24 of the purebred founding boars (12 Duroc and 12 Landrace), 48 of the founding Yorkshire-Landrace composite sows, 109 composite animals from generations 4 through 9, 29 composite animals from generation 15, and 30 purebred industry boars (15 Landrace and 15 Yorkshire) used as sires in generations 10 through 15. Using a combination of split reads, paired-end mapping, and read depth approaches, we identified a total of 3,538 copy number variable regions (CNVR), including 1,820 novel CNVR not reported in previous studies. The CNVR covered 0.94% of the porcine genome and overlapped 1,402 genes. Gene ontology analysis identified that CNV-overlapped genes were enriched for functions related to organism development. Additionally, CNVR overlapped with many known quantitative trait loci (QTL). In particular, analysis of QTL previously identified in the USMARC herd showed that CNVR were most overlapped with reproductive traits, such as age of puberty and ovulation rate, and CNVR were significantly enriched for reproductive QTL.